2012
DOI: 10.1097/bor.0b013e3283585731
|View full text |Cite
|
Sign up to set email alerts
|

Update

Abstract: Recent advances in understanding the pathogenesis of IIM have led to discovery of molecules that are candidate biomarkers of disease activity. Type 1 interferon and myeloid-cell signatures are leading candidate markers for use in IIM activity monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 47 publications
1
1
0
Order By: Relevance
“…For instance, the aberrant neutrophil extracellular trap (NET) formation may be involved in the pathogenesis of ILD in DM patients ( Peng et al, 2018 ), and proteinase 3, one type of neutrophil serine proteinases, is lower in patients of DM without ILD ( Gao et al, 2018 ). We also confirmed previous observations related to the pathogenesis of DM and DM-ILD, including the presence of the cytokine–cytokine receptor interaction ( Zhu et al, 2017 ; Chen et al, 2018 ), IL−17 signaling pathway ( Nasr et al, 2012 ). Additionally, we observed that complement and coagulation cascade pathway may play a critical role in DM-ILD.…”
Section: Discussionsupporting
confidence: 91%
“…For instance, the aberrant neutrophil extracellular trap (NET) formation may be involved in the pathogenesis of ILD in DM patients ( Peng et al, 2018 ), and proteinase 3, one type of neutrophil serine proteinases, is lower in patients of DM without ILD ( Gao et al, 2018 ). We also confirmed previous observations related to the pathogenesis of DM and DM-ILD, including the presence of the cytokine–cytokine receptor interaction ( Zhu et al, 2017 ; Chen et al, 2018 ), IL−17 signaling pathway ( Nasr et al, 2012 ). Additionally, we observed that complement and coagulation cascade pathway may play a critical role in DM-ILD.…”
Section: Discussionsupporting
confidence: 91%
“…Pregnancy induces profound immunologic alterations that establish maternal tolerance of the semi-allogeneic fetal “graft”, but also may result in dampening of maternal protective antibody responses to infection or anti-viral vaccination [39][40]. We observed a vaccine-induced fold-increase (2.0) in influenza-specific CD4 T cells among pregnant subjects that was lower than in non-pregnant subjects (2.5 fold)[30], and at the low end of the range of vaccine-induced CD4 changes reported by others for non-pregnant healthy adults [36, 4142].…”
Section: Discussionmentioning
confidence: 99%